Jakość tłumaczenia polskiego i adaptacji kulturowej kwestionariusza PRTEE (Patient–Rated Tennis Elbow Evaluation) = Quality of polish translation and cultural adaptation of PRTEE (Patient–Rated Tennis Elbow Evaluation) - Goguł, Paweł; Latosiewicz, Robert; Goguł, Magdalena; Majewska, Daria; Gawęda, Krzysztof (Journal of Education, Health and Sport, 2016)
Goguł Paweł, Latosiewicz Robert, Goguł Magdalena, Majewska Daria, Gawęda Krzysztof. Jakość tłumaczenia polskiego i adaptacji kulturowej kwestionariusza PRTEE (Patient–Rated Tennis Elbow Evaluation) = Quality of polish translation and cultural adaptation of PRTEE (Patient–Rated Tennis Elbow Evaluation). Journal of Education, Health and Sport. 2016;6(6):424-435. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.55877 http://ojs.ukw.edu.pl/index.php/johs/article/view/3590 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 16.06.2016. Jakość tłumaczenia polskiego i adaptacji kulturowej kwestionariusza PRTEE (Patient–Rated Tennis Elbow Evaluation) Quality of polish translation and cultural adaptation of PRTEE (Patient–Rated Tennis Elbow Evaluation) Paweł Goguł1, Robert Latosiewicz1, Magdalena Goguł2, Daria Majewska3, Krzysztof Gawęda3 1Zakład Rehabilitacji i Fizjoterapii, Uniwersytet Medyczny w Lublinie 2Dział Diagnostyki Obrazowej, Samodzielny Publiczny Zakład Opieki Zdrowotnej Ministerstwa Spraw Wewnętrznych i Administracji w Lublinie 3Klinika Ortopedii i Traumatologii Katedry Ortopedii, Uniwersytet Medyczny w Lublinie 1Department of Rehabilitation and Physiotherapy, Medical University of Lublin 2Department of Diagnostic Imaging, Ministry of the Interior and Administration Healthcare Center in Lublin 3Department of Orthopaedics and Traumatology, Medical University of Lublin Słowa kluczowe: łokieć tenisisty, terapia tkanek miękkich, tłumaczenie. Key words: tennis elbow, soft tissue therapy, translation. Streszczenie Wprowadzenie i cel pracy: Łokieć tenisisty jest częstym schorzeniem, dla którego nie opracowano w języku polskim zwalidowanych kwestionariuszy oceny stopnia zaawansowania. Pierwszym kwestionariuszem stworzonym do oceny łokcia tenisisty jest PRTEE (Patient–Rated Tennis Elbow Evaluation). Narzędzie to jest dostępne w języku angielskim, nie ma oficjalnej polskiej wersji tego kwestionariusza. Celem tego badania była ocena tłumaczenia i adaptacji kulturowej polskiej wersji kwestionariusza PRTEE. Materiał i metody: Jakość tłumaczenia PRTEE na język polski została oceniona za pomocą anonimowej ankiety, przygotowanej na potrzeby badania. Kwestionariusz ankiety liczył 11 pytań i krótką metryczkę. Kwestionariusze zostały wypełnione przez losowo wybrane osoby związane z fizjoterapią. Do analizy zakwalifikowano 67 prawidłowo wypełnionych ankiet. Wyniki: 62 z 67 ankietowanych (92%) stwierdziło iż polska wersja kwestionariusza jest dla nich zrozumiała. Większość ankietowanych (76%) oceniła celująco (6) i bardzo dobrze (5) zgodność polskiego kwestionariusza z wersją angielską, a wraz ze wzrostem poziomu znajomości języka angielskiego rosła ocena zgodności tłumaczenia kwestionariusza (rho=0,267; p=0,029). Zdaniem 92% ankietowanych polskie tłumaczenie kwestionariusza PRTEE nie zawiera błędów językowych (p=0,000, χ2=48,493). Wnioski: 1. Polskie tłumaczenie kwestionariusza PRTEE jest wiarygodnym językowo narzędziem do oceny funkcjonowania pacjentów z zespołem „łokcia tenisisty”. 2. Adaptacja kulturowa i polskie tłumaczenie kwestionariusza PRTEE nie zmieniają charakteru treści zawartych w angielskiej wersji kwestionariusza PRTEE. 3. Istnieje konieczność wykorzystania dokonanego tłumaczenia kwestionariusza PRTEE w praktyce klinicznej przed wystąpieniem o uznanie jej za polską wersję oficjalną. Abstract Objective: Tennis elbow is a common condition for which validated staging questionnaire in Polish has not been developed. The first questionnaire designed to assess the tennis elbow is PRTEE (Patient-Rated Tennis Elbow Evaluation). This tool is available in English, there is no official Polish version of the questionnaire. The aim of this study was to evaluate the translation and cultural adaptation of the Polish version of PRTEE. Material and methods: The quality of PRTEE translation into Polish was assessed using an anonymous questionnaire, prepared for the study. The questionnaire survey counted 11 questions and a short demographics. Questionnaires were completed by randomly selected people associated with physiotherapy. For the analysis 67 correctly completed questionnaires have been classified. Results: 62 of 67 respondents (92%) stated that the Polish version of the questionnaire is comprehensible for them. The majority of respondents (76%) assessed the compatibility of Polish and English version of questionnaire as perfect (6) and very good (5), and compatibility assessment of questionnaire translation has grown with increasing level of English proficiency (rho = 0.267; p = 0.029). According to 92% of respondents Polish translation of the questionnaire PRTEE does not contain linguistic errors (p = 0.000, χ2 = 48.493) Conclusions: 1. Polish translation PRTEE questionnaire is a linguistic reliable tool for assessing functioning of patients with "tennis elbow". 2. Cultural adaptation and Polish translation of the PRTEE questionnaire not alter the nature of the content of the English version of the PRTEE questionnaire. 3. There is a need to use translated PRTEE questionnaire in clinical practice before applying for a recognition as an official Polish version.